Libero gioco e declinazione estetica dell’immaginazione in Kant - Milli, Giulia (Aesthetica Preprint, 2023)
The relationship between imagination and understanding has a key role in Kant’s aesthetic theory. These faculties are involved in both cognitive and aesthetic judgment and make the definition of boundaries between them controversial. Accordingly, the aim of this paper is: a) to show that aesthetic judgment keeps its independence from cognitive judgment; and b) to account for an alternative kind of cognition that can be felt thanks to the aesthetic relationship between imagination and understanding. Kant points out the relationship between the faculties in the aesthetic judgment as a “free yet harmonious play”. Throughout this paper I will consider various interpretations of the free play, starting from Garroni’s model of the free play and not-free play. I will take into account Guyer’s metacognitive approach as well as Breitenbach’s interpretation, according to which the reflection of the imagination involved in aesthetic experience also plays a crucial role in the advancement of scientific cognition. However, such an approach highlights a central problem of Kantian aesthetics, namely, the ubiquity of beauty, which implies that every object of cognition must also be beautiful. In the final section, I will then discuss the aesthetic experience as different and independent from the cognitive one, which nevertheless acquires a subjective cognitive value in virtue of the feeling of pleasure: the latter makes the subject aware of the peculiar relationship between the faculties and discloses a self-awareness different from the ordinary one, working as an affective appraisal. Thus, the freedom of the imagination relies on its independence from the domain of understanding, but they still relate to each other in harmony and this interplay grants the universal yet subjective validity of the aesthetic judgment, which preserves its communicability.